تطبيق متطلبات إدارة المعرفة وأثرها علي الأداء الوظيفي لرؤساء ومنسقي الاقسام بالجامعات الخاصة(دراسة تطبيقية علي الكليات الخاصة والاهلية بمنطقة القصيم) - سليمان, ادم عبدالله; المهلاوي, سعد عثمان أحمد (جامعة الوادي - University of Eloued, 2021)
ملخص: هدفت الدراسة الي التعرف علي أثر تطبيق متطلبات إدارة المعرفة علي الأداء الوظيفي لرئيس ومنسق القسم في الجامعات الخاصة بمنطقة القصيم ، وتكونت عينة الدراسة من ) 97) رئيس ومنسق أقسام،تم أختيارهم عشوائيا ،وأستخدمت المنهج الوصفي التحليلي، والاستبانة كأداة رئيسة في الدراسة.وتوصلت الدراسة الي أستنتاجات مهمة منها: توجد علاقة ارتباط ذات دلالة إحصائية بين ادارة المعرفة والاداء الوظيفي لرئيس ومنسق القسم في مجال البحث العلمي وخدمة المجتمع لمتغيرات (الهياكل التنظيمية ، الثقافة التنظيمية،دور القيادة ، وتكنولوجيا المعلومات) . وتوصي الدراسة تبني مدخل إدارة المعرفة لتحسين الاداء الوظيفي لرئيس ومنسق القسم في مجال البحث العلمي وخدمة المجتمع،وأستخدام أساليب وأدوات وعمليات المعرفة في مجال جودة التعليم وتطويره،وتعزيز العلاقات الانسانية في مجال الهياكل التنظيمية والثقافة التنظيمية والقيادة. Abstract: Application of the Requirements of Knowledge Management and their Impact on the Job Performance of Department Heads and Coordinators in Private Universities (an Applied Study on Private and Community colleges in Al - Qassim region) This study aims at identifying the impact of applying the requirements of knowledge management on the job performance of department heads and coordinators in the private universities in Al - Qassim region. The study sample consisted of (97) department heads and coordinators, who were randomly selected. The researcher used the descriptive analytical approach and the questionnaire as a main tool in collecting data. The study came out to a number of findings including: There is a statistically significant correlation between knowledge management and the job performance of the department head and coordinator in the field of scientific research and community service with (the organizational structures, organizational culture and the role of leadership and information technology) variables. The study recommended the adoption of knowledge management input to improve the job performance of the department head and coordinator in the field of scientific research and community service, as well as using of methods, tools and processes of knowledge in the field of education quality and development, in addition to the promotion of human relations in the field of organizational structures, organizational culture and leadership.
مقال
Keywords: الهياكل التنظيمية_ القيادة_تكنولوجيا المعلومات_جودة التعليم_خدمة المجتمع; organizational structures, leadership, information technology, education quality, community service